Chemical composition and biological activities of Pimenta richardii. (23rd December 2020) - Clarke, Kellyann; Porter, Roy; Facey, Petrea; Yee, Trevor; Thoms‐Rodriguez, Camille
Abstract: Pimenta richardii is an endemic flowering plant of Jamaica belonging to the Myrtaceae family. A large number of species within this family remain phytochemically unexplored including Pimenta richardii . Hence, this study determined for the first time the chemical composition and biological activities of P richardii essential oils (EOs) extracted via hydrodistillation at four different times of the year. The EOs' chemical compositions were analyzed by gas chromatography‐mass spectrometry (GC‐MS) and GC coupled to a flame ionization detector (GC‐FID). A total of 40 compounds were identified in the P richardii EOs by comparison of the Kováts retention indices (RI), mass spectra data with those in the National Institute of Standards and Technology (NIST) library, and co‐elution with authentic samples where available. The main compounds were eucalyptol (56.53%) in April and limonene (40.7%) in July. The in vitro antimicrobial assays were performed using disk diffusion and tube dilution assay to determine the minimum inhibitory concentrations (MICs). P richardii EOs were active against all 10 micro‐organisms used including Klebsiella pneumoniae (ATCC BAA 1705), methicillin‐resistant Staphylococcus aureus — MRSA (63190122), Streptococcus group A (ATCC 19815), and Streptococcus group B (ATCC 12386) having MIC of 0.25, 0.50, 0.06, and 0.06 mg/mL, respectively. Antioxidant activities were evaluated using 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) radical scavenging assay. The EOs did not exhibit significant antioxidant property; however, there is potential use of EOs from P richardii in the pharmaceutical industry upon further evaluation. Abstract : Pimenta richardii an endemic unexplored plant of Jamaica belonging to the Myrtaceae family was studied for the chemical composition and somebiological activities of its essential oils extracted via hydrodistillationat four different times of the year. A total of 40 compounds were identified with major constituents been eucalyptol (56.53%) in April andlimonene (40.70%) in July. The oils showed antimicrobial against ten micro‐organisms assayed, however no significant antioxidant activity was observed.